(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current trends require STEM education to integrate the four disciplines (science, technology, engineering and mathematics) into a mega discipline. However, implementing integrated STEM education is not an easy task as many issues arise following its implementation. Therefore, a systematic review was conducted to gather evidence from the latest empirical studies to discover the core issues related to integrated STEM education. PRISMA guideline was used to trace the relevant article from the year 2010 until the year 2019 using databases of Wiley, Scopus and Google Scholar. Hence, a total of 17 articles were identified. Findings showed that teacher is the core issue. It implies that the teacher is the most important element in the pursuit of integrated STEM education.